Proximate characteristics and statistical optimization of ultrasound-assisted extraction of high-methoxyl-pectin from Hylocereus polyrhizus peels - Rubaiyi, M. Zaid; Mishra, Puranjan; Siti Noredyani, Abdul Rahman; Tabassum, Shabana; Zularisam, Ab Wahid; Mimi Sakinah, Abdul Munaim (Elsevier Ltd, 2020)
Ultrasound-assisted-extraction (UAE) and statistical optimization of significant process parameters for high methoxy pectin (HMP) from Hylocereus polyrhizus peels (HPP) were examined and functional properties and proximate chemical characteristics were evaluated in the present study. Statistically, the maximum yield of HMP of 31.4% with a 56.10% degree of esterification (DE) was achieved by a quadratic polynomial equation and regression analysis of 88% and 86%, respectively. The optimal observed conditions for UAE of HMP were; agitation 250 rpm, extraction temperature 65ᵒC, extraction time at 70 min, extraction solvent with pH value of 2 and LSR of 12:1 (v/w). The proximate characteristics showed 17.93% of mannose, 7.65% of rhamnose, 44.34% of galacturonic acid, 2.8% of glucose, 27.32% of galactose with 79.8% purity of the total sugar extracted from HPP. Conclusively, that the extracted HMP from HPP using UAE possesses a high yield of pectin with a significant lower extraction temperature.